Brain Changes Associated With Long-Term Ketamine Abuse, A Systematic Review - Strous, Jurriaan F. M.; Weeland, Cees J.; van der Draai, Femke A.; Daams, Joost G.; Denys, Damiaan; Lok, Anja; Schoevers, Robert A.; Figee, Martijn (Frontiers in Neuroanatomy, 2022)
Despite the promising antidepressant effects of ketamine, the safety of repeated doses remains unknown. Ketamine is associated with short-term cognitive and neuropsychiatric side-effects in clinical trials, and with neurotoxicity after repeated doses in animals. The effects of prolonged ketamine on the brain can be studied in chronic recreational users. We performed a systematic review of studies reporting functional and structural brain changes after repeated ketamine abuse. We searched the following electronic databases: Medline, Embase and PsycINFO We screened 11,438 records and 16 met inclusion criteria, totalling 440 chronic recreational ketamine users (2-9.7 years; mean use 2.4g/day), 259 drug-free controls and 44 poly-drug controls. Long-term recreational ketamine use was associated with lower grey matter volume and less white matter integrity, lower functional thalamocortical and corticocortical connectivity. The observed differences in both structural and functional neuroanatomy between ketamine users and controls, may explain some of its long-term cognitive and psychiatric side effects, such as memory impairment and executive functioning. Although the current results may not be directly translatable to clinical practice where daily dosages are on average 40 times lower than the recreational dosages reported here, our review may warrant further study of the safety of long-term ketamine administration